Role of fourteen XRE-DUF397 pairs from Streptomyces coelicolor as regulators of antibiotic production and differentiation. New players in a complex regulatory network - Riascos, Carolina; Martínez-Carrasco, Ana; Díaz, Margarita; Santamaría, Ramón I. (Frontiers in Microbiology, 2023)
Bacteria of the genus Streptomyces have a plethora of transcriptional regulators, among which the xenobiotic response element (XRE) plays an important role. In this organism, XRE regulators are often followed downstream by small proteins of unknown function containing a DUF397 domain. It has been proposed that XRE/DUF397 pairs constitute type II toxin–antitoxin (TA) systems. However, previous work carried out by our group has shown that one of these systems is a strong activator of antibiotic production in S. coelicolor and other Streptomyces species. In this work, we have studied the overexpression of fourteen XRE/DUF397 pairs present in the S. coelicolor genome and found that none behave as a type II TA system. Instead, they act as pleiotropic regulators affecting, in a dependent manner, antibiotic production and morphological differentiation on different culture media. After deleting, individually, six XRE/DUF397 pairs (those systems producing more notable phenotypic changes when overexpressed: SCO2246/45, SCO2253/52, SCO4176/77, SCO4678/79, SCO6236/35, and SCO7615/16), the pair SCO7615/16 was identified as producing the most dramatic differences as compared to the wild-type strain. The SCO7615/16 mutant had a different phenotype on each of the media tested (R2YE, LB, NMMP, YEPD, and MSA). In particular, on R2YE and YEPD media, a bald phenotype was observed even after 7 days, with little or no actinorhodin (ACT) production. Lower ACT production was also observed on LB medium, but the bacteria were able to produce aerial mycelium. On NMMP medium, the mutant produced a larger amount of ACT as compared with the wild-type strain.